2021
DOI: 10.1177/09544089211002782
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the powder mixed EDM process of nickel based super alloy

Abstract: Powder Mixed Electric Discharge Machining has been the main focus of many researchers for quite a long time. The performance of EDM process has been improved significantly by using powder mixed dielectric medium. Numerous researches were undertaken to study the influence of different process parameters involved in the powder mixed EDM by experimenting with different work materials and powder combination. The objective of this work is to conduct experimental study on the powder Mixed EDM of a Nickel based super… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…The reason is linked with the reduction of Cu powder. Smaller the amount of Cu powder lower will be the production of discharge heat, and hence less amount of material eroded from the Al electrode [24]. At 1.5 g/100 ml C p , Sunflower oil gives the least value of EWR rate.…”
Section: Influence Of Input Variables For Ewrmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason is linked with the reduction of Cu powder. Smaller the amount of Cu powder lower will be the production of discharge heat, and hence less amount of material eroded from the Al electrode [24]. At 1.5 g/100 ml C p , Sunflower oil gives the least value of EWR rate.…”
Section: Influence Of Input Variables For Ewrmentioning
confidence: 99%
“…It was revealed that the BC 4 significantly enhances the corner accuracy (43.66%) and MRR (28.46%) compared to other three powders. Ramesh and Jenarthanan [24] optimized the control variables, namely, C p , I p , and duty factor, for material removal mechanism and surface finish in PM-EDM using kerosene dielectric, and three powders, namely, graphite, manganese (Mn), 6 and silicon (Si). 7 Their findings highlighted the supremacy of the graphite powder for MRR and silicon powder for surface finish.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly in the electrical discharge turning, it is very difficult to regulate a single best set of machining parameters, as the parameters influence machinability indicators in many ways. In order to reach the mentioned solution, it should be done with multiple optimization methods for example the gray relational analysis approach [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Experimental methodologies, modeling, and optimization techniques play a critical role in such situations. For this reason, researchers have approached various statistical (Yildiz et al, 2012;Sivam et al, 2013;Uyyala et al, 2014;Gohil and Puri, 2016;Singh et al, 2019;Chaudhury and Samantaray, 2021) and computational (Bharathi Raja et al, 2013;Garcia Rojas et al, 2013;Cakir et al, 2013;Mohanty et al, 2017;Sahu et al, 2020;Ramesh and Jenarthanan, 2021) methods in their works for predictive modelling (Puertas and Perez, 2003;Keskin et al, 2005;Markopoulos et al, 2008;Gao et al, 2008;Chattopadhyay et al, 2009;Pradhan et al, 2009;Shabgard et al, 2009;Gopalakannan and Senthilvelan, 2013;Yadav and Yadava, 2014;Kumar et al, 2014;Majumder, 2014;Talla et al, 2015;Selvarajan et al, 2017;Belloufi et al, 2020), parametric optimization (Singh, 2012;Bharti et al, 2012;Tang and Guo, 2013;Tang and Du, 2014;Prabhu et al, 2013;Tzeng and Chen, 2013;Reddy et al, 2014;Singh et al, 2015;Marichamy et al, 2016;Prakash et al, 2016;R...…”
Section: Introductionmentioning
confidence: 99%